At the desert's green edge an ethnobotany of the Gila River Pima - Rea, Amadeo M. (University of Arizona Press, 2016)
"The Akimel O'odham, or Pima Indians, of the northern Sonoran Desert continue to make their home along Arizona's Gila River despite the alarming degradation of their habitat that has occurred over the past century. The oldest living Pimas can recall a lush riparian ecosystem and still recite more than two hundred names for plants in their environment, but they are the last generation of Akimel O'odham who grew up subsisting on cultivated native crops or wild-foraged plants." "Ethnobiologist Amadeo M. Rea has written the first complete ethnobotany of the Gila River Pima and has done so from the perspective of the Pimas themselves. At the Desert's Green Edge weaves the Pima view of the plants found in their environment with memories of their own history and culture, creating a monumental testament to their traditions and way of life." "At the Desert's Green Edge is an archive of otherwise unavailable plant lore that will become a benchmark for botanists and anthropologists. Enhanced by more than one hundred brush paintings of plants, it is written to be useful to nonspecialists and to be a resource for the Pimas regarding their former lifeways."--Jacket.